2016
DOI: 10.3109/08820139.2016.1168830
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of MAPKs/NF-κB Activation Induces Intestinal Anti-Inflammatory Action of Ginsenoside Rf in HT-29 and RAW264.7 Cells

Abstract: This study investigated the intestinal anti-inflammatory action of ginsenoside Rf in inflammatory bowel disease (IBD). IBD is a chronic inflammatory disease that affects the intestinal tract. It is associated with elevated levels of various inflammatory mediators, including interleukin (IL)-1β, IL-6, tumor necrosis factor-α (TNF-α), nitric oxide (NO), and reactive oxygen species (ROS). Ginsenosides, the main active constituents of ginseng, have been reported to exert potent therapeutic effects against diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 34 publications
0
39
0
4
Order By: Relevance
“…Nuclear translocation, NF‐κB phosphorylation, and DNA binding are three important events in the final stage of NF‐κB pathway activation and have been shown to be inhibited by ginsenosides under various conditions. Nuclear translocation of NF‐κB p65 can be blocked by Rg1, 20( S )‐protopanaxatriol, Rh1, Rh2, Rb1, CK, Rg3, PF11, Rf, Rd, and Rb3 . The phosphorylation of NF‐κB p65 was found to be inhibited by Rg1, Rg3, and Ro .…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 93%
See 4 more Smart Citations
“…Nuclear translocation, NF‐κB phosphorylation, and DNA binding are three important events in the final stage of NF‐κB pathway activation and have been shown to be inhibited by ginsenosides under various conditions. Nuclear translocation of NF‐κB p65 can be blocked by Rg1, 20( S )‐protopanaxatriol, Rh1, Rh2, Rb1, CK, Rg3, PF11, Rf, Rd, and Rb3 . The phosphorylation of NF‐κB p65 was found to be inhibited by Rg1, Rg3, and Ro .…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 93%
“…Activated NF‐κB eventually binds to κB elements in the promoter region of target genes and initiates the transcriptional process of numerous genes . Recent investigations have demonstrated that the NF‐κB pathway is suppressed by a large number of ginsenosides, including Rg1, Rh2, Rb1, Compound K (CK), Rg3, Rb3, Rd, Pseudoginsenoside‐F11 (PF11), Re, Rh1, Rf, 20( S )‐protopanaxatriol, and Ro (Fig. ).…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
See 3 more Smart Citations